The impact of extension delivery through private local service providers on production outcomes of small-scale aquaculture farmers in Bangladesh - Obi, Chinedu; Manyise, Timothy; Brako Dompreh, Eric; Khondker, Murshed-E-Jahan; Rossignoli, Cristiano (Informa UK Limited, 2025)
Purpose: This study delves into the effectiveness of local service providers (LSP) in improving production outcomes of small-scale aquaculture farmers in Bangladesh. Design/methodology/approach: To gauge the effectiveness of LSPs, the research employs a performance based assessment approach, focusing on 1653 fish farming households distributed across four different participation levels. Essentially, it compared quantifiable variables like the number of species cultured, productivity, proportion of fish sold and revenue metrics of the LSP-trained farmers against a control group that has not received training from LSPs. Data analysis was conducted with Multivalued Treatment Effects (MTE) estimated using an augmented inverse-probability weighting method that allows for heterogeneous treatment effects. Findings: Findings revealed that farmers who received the LSP extension training exhibited a significant increase in all outcomes compared to their counterparts. The LSP extension participating farmers are more likely to adopt better management practices like improved feeding routines, dike constructions, pond cleanliness, and fish growth monitoring. Practical implications: LSP extension model with enhanced capacity can be a catalyst for improved production of small-scale aquaculture farmers. Theoretical implications: This study contributes to a research agenda related to the efficiency of emerging pluralistic extension service systems that favors decentralization, privatization, and outsourcing of extension service, and their capability to enhance the production outcomes of small-scale farmers. Originality/value: This study addresses an important research gap in the agricultural extension literature, which is the value-for money of Local Service Providers, and their capability to enhance the production outcomes of small-scale farmers.